2019
DOI: 10.1016/j.tmp.2019.100577
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant food waste and the determinants of its effective management in Bulgaria: An exploratory case study of restaurants in Plovdiv

Abstract: Restaurant food waste represents a significant societal challenge in transitional economies where the frequency of dining out is rising. The problem of restaurant food waste in this context is however underresearched which hampers understanding of its causes and effects. This paper contributes to knowledge with a case study of food waste management in restaurants of Plovdiv in Bulgaria, a transitional economy in SouthEastern Europe. Through the lens of qualitative research, it establishes the causes of restaur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 98 publications
3
47
0
4
Order By: Relevance
“…It is an essential topic of environmental, societal, and economic concern [2]. In recent years, it has gained growing public, academic, and political attention [3]. Parfitt, Barthel, and Macnaughton [4] stated that food waste can happen at any stage of the food supply chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an essential topic of environmental, societal, and economic concern [2]. In recent years, it has gained growing public, academic, and political attention [3]. Parfitt, Barthel, and Macnaughton [4] stated that food waste can happen at any stage of the food supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the food service sector have focused on food waste management operations and reducing the amount of food waste, rather than on consumer food waste behavior in restaurants [17,18]. Parfitt et al [19] point out that consumers' plate waste in restaurants is one of the crucial sources of "away-from-home" waste, and the majority of the food waste comes from the food service sector, which highlights an important opportunity to change consumer behavior [3].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Shanghai, China, interviewed managers and chefs from the fine dining foodservice sector who reported that this kind of service causes not only excessive waste generation at the cooking stage for aesthetic purposes but also at the consumer level [38]. Besides, plate food waste at fine diners is potentially caused by the greediness of fine dining restaurant guests who commonly worry less about their expenses and end up wasting more due to over-ordering; which in turn is encouraged because of the extensive menus developed to enhance customer satisfaction and to stand out from competitors [35,39,40]. This can be further explained given the traditions of our culture, where Lebanese people over-order out of generosity as a welcoming gesture.…”
Section: Plos Onementioning
confidence: 99%
“…Importantes contribuições também são apresentadas por Thyberg e Tonjes (2016), Heikkilä et al (2016), Filimonau et al (2019) e Filimonau et al (2020) sobre desperdícios de alimentos, medidas preventivas, mudanças comportamentais individuais e nas organizações (serviços gastronômicos).…”
Section: Introductionunclassified
“…Também destaca que o desperdício de alimentos é gerenciável e deve ser um componente do sistema de gestão de uma organização. Filimonau et al (2019) comenta a importância dos restaurantes se apropriarem dos conhecimentos acadêmicos da área da Nutrição, no sentido de controlar e diminuir o tamanho das porções, contribuindo com estilos de vida saudáveis de seus clientes com menores preços. Quando necessário, os autores destacam, que os restaurantes podem oportunizar a seus consumidores a pedir mais comida, porém, pagando extra.…”
Section: Introductionunclassified